Marketing strategy : (McGraw-Hill Education, 2005)
This flexible introduction to the concepts and theories of creating and implementing a marketing strategy focuses on the strategic planning process and marketing's cross/inter-functional relationships. This book will help you integrate what you are learning about analytical tools and the 4Ps of marketing within a broader framework of competitive strategy.